Existentie vzw 2007 : Labo 5 - Existentie, Gent; De Jaeger, Christophe; Vermeulen, Pieter (Gent : Existentie vzw Gent, 2007)
Bakker, Joost; Hoogerwerf, Arnold; Kreutzberger, Lilian; Renneboog, Lucie; Ruigrok, Imke; Serneels, Stefan; Thiébaut, Boris
Publicatie n.a.v. de activiteiten van Existentie in Gent, 2007-2008
boek